2019
DOI: 10.1016/j.ijms.2018.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-carbon bond formation in the reaction of hydrated carbon dioxide radical anions with 3-butyn-1-ol

Abstract: Electrochemical activation of carbon dioxide in aqueous solution is a promising way to use carbon dioxide as a C1 building block. Mechanistic studies in the gas phase play an important role to understand the inherent chemical reactivity of the carbon dioxide radical anion. Here, the reactivity of CO2 •− (H2O)n with 3-butyn-1-ol is investigated by Fourier transform ion cyclotron (FT-ICR) mass spectrometry and quantum chemical calculations. Carbon-carbon bond formation takes places, but is associated with a barr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 98 publications
(104 reference statements)
0
6
0
Order By: Relevance
“…Upon solvation with molecules such as neutral CO 2 , H 2 O, or both, however, it turns into a stable species. The carbon dioxide radical anion is highly reactive and forms C−C bonds in the reaction with allyl alcohol, methyl acrylate, and 3‐butyn‐1‐ol . Evidence for HOCO .…”
Section: Introductionmentioning
confidence: 99%
“…Upon solvation with molecules such as neutral CO 2 , H 2 O, or both, however, it turns into a stable species. The carbon dioxide radical anion is highly reactive and forms C−C bonds in the reaction with allyl alcohol, methyl acrylate, and 3‐butyn‐1‐ol . Evidence for HOCO .…”
Section: Introductionmentioning
confidence: 99%
“…Photodissociation of the C–O bond in CO 2 – (H 2 O) n has been reported by Sanov and co-workers. , In aqueous solution, spectra of CO 2 – in the UV ,, have been measured, and the symmetric stretching and bending modes have recently been identified by Raman spectroscopy . In gas phase clusters, infrared spectra of CO 2 – (H 2 O) n have been obtained with up to two water molecules in the O–H stretch region. , Reactions of hydrated electrons with CO 2 directly revealed the process of reductive activation, resulting in the formation of CO 2 – (H 2 O) n . C–H, C–C, and C–S bond formation was observed with a series of reactants. Uggerud and co-workers have shown in elegant studies that ClMgCO 2 – complexes can be formed by collision induced dissociation of the oxalic acid complex, and studied the reactivity of reductively activated CO 2 . Weber and co-workers investigated reductive CO 2 activation in M – (CO 2 ) n systems by infrared spectroscopy. ,, Menges et al demonstrated the capture of CO 2 by a cationic Ni­(I) complex and characterized of the activated CO 2 molecule by cryogenic infrared spectroscopy . The Johnson group recently also characterized radical ion adducts between imidazole and CO 2 by vibrational spectroscopy …”
Section: Introductionmentioning
confidence: 79%
“…1621 C–H, C–C, and C–S bond formation was observed with a series of reactants. 2226 Uggerud and co-workers have shown in elegant studies that ClMgCO 2 – complexes can be formed by collision induced dissociation of the oxalic acid complex, and studied the reactivity of reductively activated CO 2 . 2730 Weber and co-workers investigated reductive CO 2 activation in M – (CO 2 ) n systems by infrared spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…With the unpaired electron localized at the carbon atom, CO 2 – (H 2 O) n clusters may be expected to react with unsaturated hydrocarbons via radical addition . While ethylene and vinyl acetate are unreactive, methyl acrylate, allyl alcohol as well as 3-butyn-1-ol exhibit the expected reactivity, exemplified in reaction for methyl acrylate. CO 2 false( normalH 2 normalO false) n + normalC 2 normalH 3 COOCH 3 CO 2 normalC 2 normalH 3 COOCH 3 false( normalH 2 normalO false) n x + x normalH 2 normalO …”
Section: Hydrated Ions In the Gas Phasementioning
confidence: 99%